A new microendemic frog species of the genus Blommersia (Anura: Mantellidae) from the east coast of Madagascar - Pabijan, Maciej; Gehring, Philip-Sebastian; Köhler, Jörn; Glaw, Frank; Vences, Miguel (Zootaxa, 2011)
Field surveys in northeastern Madagascar have revealed the existence of a new Blommersia frog species (Anura: Mantellidae), populations of which were recorded within a 30 km radius of the town of Maroantsetra. We combined morphological, bioacoustic and molecular techniques and show that it is indeed a distinct evolutionary lineage which we describe as Blommersia variabilis sp. nov. from the type locality Ambodivoahangy near Maroantsetra. This new species is morphologically most similar to B. wittei by the presence of vomerine teeth and relatively small, well-delimited femoral glands, but differs from that species by advertisement call consisting of only 2–6 notes of comparatively longer duration, and a wider separation of femoral glands in males. It is associated with dense secondary vegetation fringing lentic water bodies. Anecdotal evidence suggests its life history is similar to other congeners. The restricted range of this species implies that it is microendemic, being possibly confined to the Antainambalana watershed. Mitochondrial and nuclear DNA variation show that its closest known relatives are Blommersia galani and B. dejongi, both of which also have restricted ranges on the east coast. A putative hybrid between a B. galani female and B. dejongi male with intermediate morphology was identified based on nuclear and mitochondrial DNA variation.